Are Insect Populations Inherently More Variable? A Multi‐Taxa Approach to Characterising Interannual Fluctuations in Insect Time Series - Graham A. Montgomery; Eliza M. Grames; Jake M. Jacobsen; Ethan X. Kahn; Amanda Leyel; Mia C. Rosati; Qiyuan Wu; Chris S. Elphick; David Wagner; Morgan W. Tingley (Ecology Letters, 2026)
The determinants of population variability across taxa, time, and space are not fully understood, particularly for insects, a group with recent reports of widespread abundance declines. We collated data from unpublished and published sources to calculate indices of interannual population variability for over 4500 unique insect time series, comprising data from nearly 1500 species. We evaluate whether insects exhibit greater population variability than other types of animals. Our results demonstrate that insects as a group indeed exhibit much greater population variability than birds, mammals, or fish, but that within Insecta, included orders show similar levels of population variability. We also find that population variability in insects is greater at higher latitudes, for species with smaller body sizes and for shorter, older time series and that it varies between biomes. Overall, our findings can inform the interpretation and prediction of insect population trends, fluctuations and extinction risk in an era of insect decline.